Measurement of the photometric characteristics of LEDs - Nazarenko, L.A.; Zubkov, D.P. (Вопросы атомной науки и техники, 2015)
Proposed and implemented a method for measuring LEDs, which is based on self-calibration of the LED goniophotometer facility by using a trap-detector. Designed and manufactured automated goniophotometer, which provides a measurement of high power LEDs at a specified junction temperature. Designed and experimentally researched the photometer with a photometric sphere based diffuser, which meets all requirements of CIE for photometric measurements of LEDs. Запропоновано та реалізовано метод вимірювання світлодіодів, який полягає в самокалібруванні гоніофотометричної установки для вимірювання світлодіодів за допомогою трап-детектора. Розроблено та виготовлено автоматизований гоніофотометр, який забезпечує вимірювання потужних світлодіодів при заданій температурі p-n-переходу. Розроблено та експериментально досліджено фотометр з фотометричною кулею в якості дифузора, який відповідає всім вимогам МКО для фотометричних вимірювань світлодіодів. Предложен и реализован метод измерения светодиодов, который заключается в самокалибровке гониофотометрической установки для измерения светодиодов с помощью трап-детектора. Разработан и изготовлен автоматизированный гониофотометр, который обеспечивает измерение мощных светодиодов при заданной температуре p-n-перехода. Разработан и экспериментально исследован фотометр с фотометрической сферой в качестве диффузора, который отвечает всем требованиям МКО для фотометрических измерений светодиодов.